Precautionary Savings and Global Imbalances in World General Equilibrium - Sandri, Damiano (IMF Working Papers; Working Paper, 2011)
In this paper we assess the implications of precautionary savings for global imbalances by considering a world economy model composed by the US, the Euro Area, Japan, China, oil-exporting countries, and the rest of the world. These areas are assumed to differ only with respect to GDP volatility which is calibrated based on the 1980-2008 period. The model predicts a wide dispersion in net foreign asset positions, with the highly volatile oil-exporting countries accumulating very large asset holdings. While heterogeneity in GDP volatility may lead to large imbalances in international investment positions, its impact on current accounts is much weaker. This is because countries are expected to move towards their optimal NFA at a very slow pace.